2011
DOI: 10.1007/s00192-010-1350-7
|View full text |Cite
|
Sign up to set email alerts
|

Posterior intravaginal slingplasty: efficacy and complications in a continuous series of 118 cases

Abstract: PIVS seems a safe and effective procedure for VCP and UVP. Vaginal erosion was mainly observed in patients with VCP treated with multifilament polypropylene mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
2
9
2
1
Order By: Relevance
“…However, previous studies demonstrated that correction of the posterior compartment with mesh increased cystocele incidence 19, 20 . Similarly, concomitant sacrospinous ligament fixations or posterior transvaginal mesh kits may increase the incidence of cystocele, or at least not decrease it.…”
Section: Discussionmentioning
confidence: 90%
“…However, previous studies demonstrated that correction of the posterior compartment with mesh increased cystocele incidence 19, 20 . Similarly, concomitant sacrospinous ligament fixations or posterior transvaginal mesh kits may increase the incidence of cystocele, or at least not decrease it.…”
Section: Discussionmentioning
confidence: 90%
“…The rate of de novo cystocele ranges from 5.8% to 21.3% after construction of apical support (28). Cystocele reportedly develops because of a shift in intra-abdominal pressure from the reinforced posterior compartment to the anterior compartment (29). Simultaneous reinforcement of the anterior compartment or total repair of the prolapse may reduce the development of de novo defects.…”
Section: Discussionmentioning
confidence: 99%
“…It uses a type III multifilament polypropylene tension-free tape to create an artificial uterosacral neoligament thus anchoring the apex of the prolapsed vaginal vault 1. Cure rates show wide variation, being reported to be between 71% and 91% 24. Likewise complication rates show great variability.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise complication rates show great variability. In the most recent and comprehensive review of the literature,4 common complications included vaginal and rectal erosions (8.5%), apical recurrence (6.1%), posterior recurrence (4.6%), de novo stripsis (5.3%), dyspareunia (5.2%), buttock pain (3.3%) and haematoma formation (2.6%). Rarer complications include rectal injury (0.8%) and ‘abscess and fistula’ formation (1.4%).…”
Section: Discussionmentioning
confidence: 99%